Catalase Nanocrystals Loaded with Methylene Blue as Oxygen Self‐Supplied, Imaging‐Guided Platform for Photodynamic Therapy of Hypoxic Tumors. Issue 41 (17th September 2021) - Zhou, Renbin; Ohulchanskyy, Tymish Y.; Xu, Hao; Ziniuk, Roman; Qu, Junle
Abstract: Photodynamic therapy (PDT) is a well‐known method for cancer therapy in the clinic. However, the inherent hypoxia microenvironment of solid tumors enormously restricts the PDT efficiency. Herein, catalase nanocrystals (CatCry) are introduced as in situ oxygen (O2 )‐generating system to relieve tumor hypoxia and enhance PDT efficiency for solid tumors. After loading with photosensitizer methylene blue (MB), a PDT drug platform (CatCry‐MB) emerges, allowing for significant increasing PDT efficiency instigated by three factors. First, the high stability and recyclable catalytic activity of CatCry enable a long‐term endogenous H2 O2 decomposition for continuous O2 supply for sustained relief of tumor hypoxia. Second, both the produced O2 and loaded MB are confined within CatCry nanoporous structure, shortening the diffusion distance between O2 and MB to maximize the production of singlet oxygen ( 1 O2 ). Third, the MB molecules are uniformly dispersed within CatCry lattice, avoiding MB aggregation and causing more MB molecules be activated to produce more 1 O2 . With the three complementary mechanisms, tumor hypoxia is eradicated and the resulted enhancement in PDT efficiency is demonstrated in vitro and in vivo. The proposed approach opens up a new venue for the development of other O2 ‐dependent tumor treatments, such as chemotherapy, radiotherapy, and immunotherapy. Abstract : Catalase nanocrystals (CatCry) are introduced as drug nanocarrier generating oxygen (O2 ) within hypoxic tumors. A prolonged CatCry catalytic activity enables the decomposition of intratumoral H2 O2 for O2 supply, while their nanoporosity allows to soak CatCry with the photosensitizer (PS) methylene blue. Combination of the sustained O2 supply and increased generation of singlet oxygen by PS results in enhanced photodynamic therapy.